Influence of Heat Treatments on the Content of Bioactive Substances and Antioxidant Properties of Sweet Potato (Ipomoea batatas L.) Tubers - Janette Musilova; Judita Lidikova; Alena Vollmannova; Hana Frankova; Dana Urminska; Tatiana Bojnanska; Tomas Toth (Journal of Food Quality)
Heat treatment can affect the bioactive compounds in sweet potato (SP). In this work, we monitored the influence of heat treatment (boiling, steaming, microwaving, and baking) on the total polyphenols content (TPC), total antioxidant capacity (TAC), total anthocyanins content (TANTC), and phenolics acids (chlorogenic (CGA), neochlorogenic (neo-CGA), and trans-ferulic (tFA)) in two SP varieties grown in Slovakia and Croatia. TPC, TAC, and TANT were determined spectrophotometrically and phenolic acids by HPLC. TPC ranged from 576 (Beauregard, Croatia; Be/HR) to 3828 (414-purple, Slovakia; Pu/SK) mg/kg DW in the raw SP tubers. After heat treatment, TPC increased, most in steamed SP (8438 mg GAE/kg DW; Pu/SK), while only in boiled SP (Be/HR), TPC decreased (353 mg GAE/kg DW). TAC varied from 0.848 (Be/HR) to 8.67 (Pu/HR) (μmol TE/g DW) in raw SP. The TAC increased by heat treatment (max. 14.2 μmol TE/g DW; cooking Be/SK), except for Pu/HR. The TANT ranged from 151 (raw Pu/SK) to 1276 (microwaved Pu/SK) mg CyE/kg FW. Heat treatment had a negative effect on phenolic acid content; the largest reduction was after boiling: CGA by 29% (Pu/SK), neo-CGA by 69% (Pu/HR), and tFA by 29% (Be/HR). The influence of heat treatment on the monitored quantities is not definite.